Rivaroxaban plus aspirin vs. dual antiplatelet therapy in endovascular treatment in peripheral artery disease and analysis of medication utilization of different lesioned vascular regions - Huo, SiYan; Cheng, Jun (Frontiers in Surgery, 2023)
In the management of Peripheral Arterial Disease (PAD), the administration of anticoagulant or antiplatelet agents is imperative. The use of Dual Antiplatelet Therapy (DAPT) in conjunction with rivaroxaban has shown potential in mitigating adverse outcomes. Given the heterogeneity in the pathology of lower limb arteries, there is a compelling case for individualized treatment strategies.In a single-center retrospective study on pharmacotherapy for peripheral artery disease, patients were treated with either aspirin combined with rivaroxaban or aspirin coupled with clopidogrel. The primary efficacy outcome encompassed a composite of increases in the Rutherford classification, acute limb ischemia, amputations due to vascular causes, target lesion revascularization, myocardial infarction, ischemic stroke, and cardiovascular death. The primary safety outcome was major bleeding, as defined by the Thrombolysis in Myocardial Infarction (TIMI) criteria; Major bleeding as categorized by the International Society on Thrombosis and Haemostasis (ISTH) served as a secondary safety outcome. The study differentiated between two subgroups: patients with only above-the-knee and below-the-knee arterial lesions.From January 2016 to December 2021, 455 patients received either clopidogrel plus aspirin or rivaroxaban plus aspirin following endovascular treatment (EVT). The rivaroxaban group (n=220) exhibited a lower incidence of primary efficacy outcomes (49.1% vs 60.4%, hazard ratio (HR) 0.77, P=0.006) but had more TIMI major bleeding events (5.9% vs 2.1%, HR 2.6, P=0.04). ISTH major bleeding events did not show a significant difference, though a higher percentage of rivaroxaban patients discontinued medication due to bleeding (10% vs 4.7%, HR 2.2, P=0.03). In the above-the-knee arterial disease subgroup, the rivaroxaban group demonstrated a lower incidence of primary efficacy outcomes (28.2% vs 45.2%, HR 0.55, P=0.02). In the below-the-knee arterial disease subgroup, no significant difference was observed in the occurrence of primary efficacy events between the two groups (58.7% vs 64.8%, HR 0.76, P=0.14).Rivaroxaban plus aspirin improved outcomes compared to DAPT in patients with lower extremity artery disease. Similar findings were observed in the above-the-knee artery lesion-only group. However, in the below-the-knee artery lesion-only group, rivaroxaban plus aspirin did not surpass DAPT in efficacy. Regarding safety, rivaroxaban plus aspirin exhibited higher bleeding risks and more frequent treatment discontinuation than aspirin combined with clopidogrel.